2010
DOI: 10.1002/art.27460
|View full text |Cite
|
Sign up to set email alerts
|

Breaking T cell tolerance against self type II collagen in HLA–DR4–transgenic mice and development of autoimmune arthritis

Abstract: epitope is clearly immunodominant in both tolerized and nontolerized DR4 mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 48 publications
(62 reference statements)
3
38
1
Order By: Relevance
“…Citrullinated peptides and their native counterparts were chosen based on studies that demonstrated ACPA presence and its ability to elicit T cell responses in HLA-DR shared epitope-positive patients with RA. These were citrullinated vimentin 66-78 (SAVRLRSSVPGVR) (18,21,22), citrullinated aggrecan 89-103 (ATEGRVRVNSAYQDK), citrullinated CILP 297-311 (ATIKAEFVRAETPYM), citrullinated a-enolase [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] (IFDSRGNPTVEVDLF) (20), and unmodified collagen 258-272 (PGIAGFKGEQGPKGE) (23,24), where the underlined arginine indicates the native amino acid that was replaced with citrulline. As a reference control for HLA class II binding, we also tested hemagglutinin A (HA) 306-318 (PKYVKQNTLKLAT).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Citrullinated peptides and their native counterparts were chosen based on studies that demonstrated ACPA presence and its ability to elicit T cell responses in HLA-DR shared epitope-positive patients with RA. These were citrullinated vimentin 66-78 (SAVRLRSSVPGVR) (18,21,22), citrullinated aggrecan 89-103 (ATEGRVRVNSAYQDK), citrullinated CILP 297-311 (ATIKAEFVRAETPYM), citrullinated a-enolase [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] (IFDSRGNPTVEVDLF) (20), and unmodified collagen 258-272 (PGIAGFKGEQGPKGE) (23,24), where the underlined arginine indicates the native amino acid that was replaced with citrulline. As a reference control for HLA class II binding, we also tested hemagglutinin A (HA) 306-318 (PKYVKQNTLKLAT).…”
Section: Methodsmentioning
confidence: 99%
“…We measured binding of native and citrullinated forms of vimentin [66][67][68][69][70][71][72][73][74][75][76][77][78] and a-enolase [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and noncitrullinated type II collagen [258][259][260][261][262][263][264][265][266][267][268][269][270][271][272] to 88 class II alleles on Luminex beads (which includes alleles of many varying degrees of susceptibility and resistance). We expressed DRB1*04:01, *04:02, and *08:01 in T2 cells and mutated DRB1*04:01 at positions 67, 70, 71, 74, and 86 to corresponding residues in DRB1*04:02, *04:03, *04:04, *04:05, and *08:01.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment in B10.DR4 Ncf1*/* mice was reproduced using an altered immunization protocol: 100 g protein emulsified in CFA (primary immunization, day 0) and 100 g protein in Freund's incomplete adjuvant (IFA; Difco) (boost, day 21), both injected intradermally at the base of the tail. We further tested the same immunization protocol in HLA-DR4-transgenic mice on a C3H background (C3H.DR4, which are more susceptible to CIA than B10.DR4 mice) (6), and in HLA-DR1-transgenic mice (7) on the B10 background (B10.DR1). HLA-DR1 alleles show association with CEP-1 antibodies in RA, although the association is weaker than that observed with HLA-DR4 alleles (1).…”
Section: To the Editormentioning
confidence: 99%